Short Practical Regimen of Acupuncture for Melasma: A Prospective Cohort Study in a Tertiary Hospital in Thailand - Supasiri, Thanan; Salakshna, Nuntida; Pongpirul, Krit (Frontiers in Public Health, 2021)
Background: Acupuncture shows benefits for patients with melasma, although no optimal number of sessions have been determined. Methods: Prospective observational study was conducted in melasma patients who were treated with acupuncture procedures twice a week and were evaluated after the fifth and the tenth sessions of acupuncture, with a one-week follow-up after the last session. Participants Groups A and B received five and ten acupuncture sessions, respectively. Melasma was assessed by using the Melanin Index (MI), Melasma Area and Severity Index (MASI), patient-reported improvement scores, and acupuncture-related adverse events. Results: Of 113 participants, 67 received five sessions of acupuncture treatment while 39 received ten sessions. At one week after five sessions of acupuncture in Group A, the mean MI decreased by 28.7 (95%CI -38.5 to -18.8, p<0.001), whereas the median MASI decreased by 3.4 (95%CI -6.9 to -1.2, p<0.001) points. At one week after ten sessions of acupuncture in Group B, the mean MI decreased by 31.3 (95%CI -45.0 to -17.6, p<0.001), whereas the median MASI decreased by 5.4 (95%CI -9.9 to -3.0, p<0.001) points. The first five sessions of acupuncture had a higher incremental effect than the last five sessions, although there was no statistically significant difference. Twenty-nine participants reported minor side effects. Group B had a risk ratio (RR) of having adverse events 1.8 times (95% CI 1.0-3.4, p=0.05) compared to Group A. Conclusion: Short acupuncture regimen of five to ten sessions in melasma seems to be effective and practical with minor side effects.